Evaluation of spark plasma sintered (SPS) hydroxyapatite powders - Chow, Vicky Yuen San. (2008)
The effects of particle sizes (<20 micrometers, 20-45 micrometers, 45-75 micrometers and 75-125 micrometers) of starting powders and isothermal sintering duration on the mechanical properties, phase composition and bioactivity of spark plasma sintered (SPS) hydroxyapatite(HA) pellets are studied and evaluated in this project.